Civil aviation policies and practices in Turkey in a global context through sustainable aviation - GÜRSOY HAKSEVENLER, BETÜL HANDE (My University, 2023)
The negative environmental effects of global civil aviation growth since the 19th century lead to the emergence of the \"sustainable aviation\" concept. This study aims to determine the current status of sustainability discussions in developing Turkish civil aviation and its alignment with global sustainable aviation policies. The research data are collected through document analysis and key expert interviews. Document analysis is to review reports on sustainable aviation and to compare two cases of AirFrance-KLM and Turkish Airlines. Semi-structured interviews are conducted with key experts from airline companies, public institutions, and subsidiary services in the Turkish aviation sector. The analysis results are presented under the themes of \"institutional, conceptual, Turkey\"s current situation, motivations, role of international organizations, cooperation and coordination, problems and obstacles.\" The results show that the Turkish civil aviation industry is enthusiastic about catching up with international standards and is successful in keeping up with the latest technologies. The private sector is leading the sector by targeting global competitiveness. Current deficiencies stem from legislation, incentives, obligations, resources, and environmental awareness. The main contribution is to be the first source and guide for future studies that aim to shed light on policymaking in Turkey as an emerging country case.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; case comparison; civil aviation; document analysis; interview; sustainability; Turkey